PHYSICAL CULTURE AND ORTHODOXY - Orishev A.B.; Kortunov V.V.; Mamedov A.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the attitude of the Russian Orthodox Church (its teachings) to physical culture and sports. Methods and structure of the study. The included and non-participated observation of athletes, interviews of Orthodox priests, content analysis of the speeches of church hierarchs, and a sociological survey of 300 young people aged 17 to 23 involved in physical education at the Timiryazev Academy were used. Results and conclusions. Various points of view on the problem under study are given, the role of physical culture and sports in the spiritual development of an Orthodox person is considered. The authors draw attention to the fact that physical activity, keeping one’s body in an active state contribute to spiritual service, as well as the spread of Orthodox Christian values. The statement is substantiated that physical activity provides invaluable assistance in the spiritual life of a modern person. It is noted that Orthodox hierarchs say that by going in for sports, maintaining physical activity, a person not only takes care of his own health, but also helps his loved ones in social terms. The main scientific result is that the authors managed to prove that physical education is part of the path of a person’s moral perfection and one of the ways to get closer to spiritual ideals that play a big role in the life of an Orthodox person. And at present, this is precisely the position of both the official Orthodox Church and Orthodox priests, and the majority of believers.